500 low glycemic index recipes : fight diabetes and heart disease, lose weight, and have optimum energy with recipes that let you eat the foods you enjoy /: fight diabetes and heart disease, lose weight, and have optimum energy with recipes that let you eat the foods you enjoy. (©2010) - Unknown
No abstract available